Mechanical properties and microstructure of large-area diamond/silicon bonds formed by pressure-assisted silver sintering for thermal management. (March 2023) - Zhao, Kechen; Zhao, Jiwen; Wei, Xiaoyun; Zhang, Xu; Deng, Chaojun; Yang, Yong; Cao, Wenxin; Han, Jiecai; Dai, Bing; Zhu, Jiaqi
Abstract: Ag sinter pastes comprising Ag nano/microparticles in an organic binder exhibit many advantages for electronic packaging, such as a low sintering temperature (<300 °C), high melting point (960 °C) after sintering, and high thermal conductivity (>100 W/mK). In this research, we prepared large-area (27 × 28 mm 2 ) Si chip/diamond heat spreader systems with low thermal interface resistance (TIR) and high bonding strength by pressure-assisted Ag sintering at 220 °C. Chemical oxidation and Ar plasma pre-treatments were conducted to enhance the oxygen and sp 2 terminations of the diamond surface. Furthermore, because of the importance of bonding pressure and temperature for industrial applications, we studied the effect of applied pressure on bond quality and TIR. The lowest TIR (0.428 mm 2 K/W) and maximum shear strength (above 50 MPa, in tests of the 5 × 5 mm 2 size) of the Si/diamond bond systems were obtained by using a bonding pressure of 10 MPa. This study reveals the potential of pressure-assisted Ag sintering for connecting diamond heat spreaders in various electronic assemblies with stable bonds for the thermal management of high-power devices. Graphical Abstract: ga1 Highlights: A reliable bonding of large-area diamond and Si chips by sintered silver paste is introduced. The applied sintering pressure could significantly affect the microstructure and performance of the joint. The sintered joints exhibit a low thermal interface resistance (＜1 mm 2 K/W) and high bonding strength (＞30 MPa). We evaluate the heat dissipation capability for this strategy to practice application.